Gender gaps in National Institutes of Health dermatology grant recipients - Alyssa M. Thompson, BS; Kyla N. Price, BS; Swetha Atluri, BS; Danielle Yee, MD; Jennifer L. Hsiao, MD; Vivian Y. Shi, MD (Wolters Kluwer, 2021)
Background: Understanding the demographics and scholarly merit among National Institutes of Health (NIH) award recipients can help guide future applicants in the field of dermatology. Objective: Herein, we aimed to explore gender gaps in NIH award recipient demographics and scholarly merits for dermatology-related projects. Methods: Projects funded by the National Institutes of Arthritis and Musculoskeletal and Skin Diseases between 2015 and 2019 related to dermatology were extracted using the NIH Research Portfolio Online Reporting Tools database. The number of publications and h-index of each award recipient were collected using the Scopus database. The 2019 Blue Ridge Institute for Medical Research report was used to determine the top 20 NIH-funded dermatology departments/divisions. Results: Between 2015 and 2019, there were 35.1% more unique male than unique female recipients. Award recipients had an average of 116.7 total publications and an average h-index of 37.1. However, men also had more than half as many publications and a >37% higher average h-index. Gender gaps in research merit, as well as number and type of awards, are reduced among recipients affiliated with a top 20 NIH-funded institution. Conclusion: A higher number of awards were granted to male recipients. Men had a higher mean publication number and h-index compared with their female counterparts. Increased support, resources, and mentorship opportunities to women in research may help mitigate these gaps.